2021
DOI: 10.3390/ani11102938
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of the Histopathologic Diagnosis of Concurrent Duodenal and Ileal Biopsy Specimens in Dogs

Abstract: Histopathologic discordance between gastrointestinal (GI) locations in canine chronic inflammatory enteropathy (CIE) has prompted recommendations to biopsy both the duodenum and ileum, while further evaluation is required for non-CIE. We aimed to determine the concordance of histopathologic diagnosis between duodenal and ileal endoscopic or full-thickness biopsy specimens for all dogs with CIE and GI neoplasia and to assess the association between histopathologic discordance between GI locations with clinicopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 37 publications
4
7
1
Order By: Relevance
“…An early study in dogs found that the concordance of histologic diagnosis between duodenal and ileal sites was high for lymphoplasmacytic enteritis (73%) but low for eosinophilic enteritis (17%). 3 The same study also confirmed the discordance between upper and lower gastrointestinal biopsies for smallcell lymphoma in dogs. 3 In our opinion, these are compelling reasons to perform ileoscopy.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…An early study in dogs found that the concordance of histologic diagnosis between duodenal and ileal sites was high for lymphoplasmacytic enteritis (73%) but low for eosinophilic enteritis (17%). 3 The same study also confirmed the discordance between upper and lower gastrointestinal biopsies for smallcell lymphoma in dogs. 3 In our opinion, these are compelling reasons to perform ileoscopy.…”
Section: Discussionsupporting
confidence: 58%
“…3 The same study also confirmed the discordance between upper and lower gastrointestinal biopsies for smallcell lymphoma in dogs. 3 In our opinion, these are compelling reasons to perform ileoscopy. Nevertheless, in those cases in which CIE was the diagnosis and endoscopy did not include ileoscopy, this study and cobalamin concentration might provide the clinician with insight into the ileum's condition.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Thus, the quality and extent of pinch biopsies are inferior to that of full-thickness biopsies, potentially leading to incorrect diagnoses. [76][77][78] Dogs in all groups had biopsies evaluated by a pathologist at a reference laboratory, however, we did not have a single pathologist review all samples. Even though the interobserver variation between pathologists can be significant, 79 histopathologic scoring was not an objective of this study, and was not pursued further.…”
Section: Discussionmentioning
confidence: 99%
“…Though endoscopy is noninvasive and might facilitate localization of lesions, the endoscope is rarely able to access the jejunum, and in some dogs, it can be challenging to gain access to and obtain biopsies from the ileum. Thus, the quality and extent of pinch biopsies are inferior to that of full‐thickness biopsies, potentially leading to incorrect diagnoses 76‐78 . Dogs in all groups had biopsies evaluated by a pathologist at a reference laboratory, however, we did not have a single pathologist review all samples.…”
Section: Discussionmentioning
confidence: 99%